AIDS, Poverty, and Hunger: Challenges and Responses 2006
DOI: 10.2499/0896297586ch8
|View full text |Cite
|
Sign up to set email alerts
|

HIV/AIDS and the Agricultural Sector in Eastern and Southern Africa: Anticipating the Consequences

Abstract: Background There is now widespread recognition that HIV/AIDS is not simply a health issue. Effectively combating the pandemic will require a coordinated multisectoral approach. Although many in the agricultural sector embrace the idea of playing a role in combating HIV/AIDS, there has been very little analysis by agricultural policy analysts to guide them. Despite the fact that the pandemic is now in its third decade in Africa, available analysis to date provides a very murky picture of how HIV/AIDS is affecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…In East Africa, HIV/AIDS affects the economically active age group resulting in loss of income, worsening poverty and reversed decades of gains in life expectancy (Buve´, Bishikwabo-Nsarhaza, & Mutangadura, 2002;Jayne, Villarreal, Pingali, & Hemrich, 2005;Piot, Bartos, Ghys, Walker, & Schwartla¨nder, 2001;UAC, 2006).…”
Section: Introductionmentioning
confidence: 97%
“…In East Africa, HIV/AIDS affects the economically active age group resulting in loss of income, worsening poverty and reversed decades of gains in life expectancy (Buve´, Bishikwabo-Nsarhaza, & Mutangadura, 2002;Jayne, Villarreal, Pingali, & Hemrich, 2005;Piot, Bartos, Ghys, Walker, & Schwartla¨nder, 2001;UAC, 2006).…”
Section: Introductionmentioning
confidence: 97%
“…The decline is caused by the illness and deaths of people living with AIDS and the time spent by household members in caring for sick relatives. In Tanzania, a study found that a woman whose husband was sick spent 45 per cent less time on agricultural tasks than a woman whose husband was healthy [35]. In Ethiopia an HIV/AIDS epidemic has caused shifts of production from cash crops to food crops in AIDS-affected households.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other strategies focus on increasing the stock and the health of animal assets within the small-scale farm sector, as well as the stock of equipment such as plows and harrows. Enhancing farmers' incentives and ability to acquire draft animals and equipment can also help alleviate the crucial labor burden of land preparation (Jayne et al 2005).…”
Section: Enhancing Household Productivitymentioning
confidence: 99%